RESEARCH ON THE TRENDS IN ANIMAL PRODUCTION IN THE LAST DECADE IN ROMANIA - Mircea Adrian GRIGORAS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper has the purpose to analyze the trends in the animal production in Romania. The empirical data were collected from the National Institute of Statistics for the period 2007-2016. Using the trend method, and indices method, it was presented the evolution of animal production value, and it share in the value of agricultural production, livestock by species, animal production: meat, milk, eggs, honey, the position of Romania in the EU-28 livestock and animal production, average consumption of animal products per inhabitant, price at farm gate and basic prices for products of animal origin, average acquisition prices for animal products and average price of animal products in the agro-food market. Animal production value declined by 30 % accounting for Lei 23.8 billion in 2016, with a share of 33.8 % in the value of agricultural production. The livestock declined in case of bovines, pigs and poultry, but increased in case of sheep, goats and bee families. The quantitative animal production decreased regarding total live weight at slaughter in case of bovines and pigs, it increased in case of poultry and remained stable in case of sheep and goats. Milk production declined, egg production remained stable and honey production increased. While meat production had a slight increase per inhabitant, meat consumption declined. Both milk production per inhabitant and milk consumption decreased. Both producer price at farm gate and the basic price for the products of animal origin registered a growth in the analyzed period, they are not enough high to cover production costs mainly in dairy and pig farms, despite of the allotted subsidies. This situation reflected a descending trend in animal production with a negative impact on the farmers' income, market offer, demand/offer ratio. Romania is not competitive in the sector of animal production with other EU countries and remains a net importing country of animal products.